The lost worlds of royal commissions in the NHS: The unaccountable in pursuit of the unanswerable?. Issue 2 (July 2019) - Powell, Martin
There have been recent calls for a royal commission (RC) on the British National Health Service (NHS). This article focuses on the impact of RCs and similar advisory bodies, particularly on finance recommendations, of three inquiries with broad remits across the whole of the NHS from very different periods: Guillebaud (1956); Royal Commission on the National Health Service (1979); and House of Lords Select Committee on the Long-term Sustainability of the NHS (2017). These inquiries appear to have had rather limited impacts, especially on NHS funding. First, there appears to be some hesitancy in suggesting precise figures for NHS expenditure. Second, the reports are advisory, and governments can ignore their conclusions. Third, governments have ignored their conclusions. In the 1950s and the 1980s, contrary to the recommendations of the inquiries, NHS expenditure subsequently grew only slowly, and charges were increased. In short, asking an independent RC to provide answers on NHS expenditure is perhaps the unaccountable in pursuit of the unanswerable.